Survivin is an independent predictor of short-term survival in poor prognostic breast cancer patients - Hinnis, A R (Nature Publishing Group, 2007)
Established clinico–pathological factors can place patients with breast cancer into good and poor prognostic categories, but even within these groups behaviour and response to treatment can differ. This study examined the value of cell cycle and apoptotic regulatory proteins in predicting behaviour in a poor prognostic group. A total of 165 patients, all of whom had died of breast cancer with duration of survival 12–127 months, median 38 months, were examined using immunohistochemistry for proliferation, apoptosis, p53, phosphorylated p53, p21, checkpoint kinase 2 (Chk2), bcl-2, bax, survivin and XIAP. All had received chemotherapy and/or hormonal therapy and were predominantly T2, node positive, grade III with only half oestrogen-receptor (ER) positive. High proliferation, phosphorylated p53, Chk2 and survivin expression correlated with grade III and lack of ER, whereas low proliferation, p21 and bcl-2 related to better grade and presence of ER. On univariate analysis grade, proliferation, phosphorylated p53, bcl-2, ER and survivin related to duration of survival. In multivariate analysis, grade (P=0.001) and survivin (P=0.005) were independent prognostic factors, grade III and presence of survivin relating to shorter survival. The latter was particularly for those patients receiving neoadjuvant therapy and adjuvant chemo- and hormonal therapy. The presence of the inhibitor of apoptosis protein survivin is a highly significant independent predictor of shorter duration of survival of patients with poor prognostic features, and merits investigation as a marker in other prognostic groups.